Powering the Future: Energy Storage in Tomorrow's Electricity Markets - Rahmat Poudineh; Dimitra Apostolopoulou (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2024)
Energy storage, encompassing not only the storage of electricity but also the storage of energy in various forms such as heat and chemicals, is a linchpin in the movement toward a decarbonized energy sector, due to its myriad roles in fortifying grid reliability, facilitating the integration of renewables, and advocating for energy efficiency and equity. Furthermore, energy storage facilitates the electrification of various sectors, including transportation and heating, promotes energy access in remote and underserved regions, and encourages the development of innovative business models and services in electricity markets. By exploring these topics, the articles in this issue of the Oxford Energy Forum (OEF) aim to stimulate insightful discussions that will influence policy, regulation, and market development, pushing forward the integration of energy storage solutions. The issue focuses on the critical function of energy storage in evolving electricity markets, highlighting its necessity in renewable integration and grid stability. It explores various storage forms, such as battery and chemical, and their role in balancing energy supply and demand both in short- as well as long-term, thus supporting a shift toward decarbonization. Additionally, it addresses the economic challenges posed by the high upfront costs, regulatory and revenue uncertainties of energy storage projects. The issue also examines different market designs and support schemes to alleviate these risks, underlining the need for innovative solutions to ensure long-term financial viability for storage investors and adapting electricity markets to accommodate the unique characteristics of storage technologies for sustainable energy system operations.
Keywords: 330